Die Regesten der Urkunden im Staatsarchiv der Freien und Hansestadt Hamburg Bd. II: 1400-1440 - Sarnowsky, Juergen (Hamburg University Press, 2021)
As in all medieval cities, writing became increasingly important in Hamburg in the course of the later Middle Ages. In addition to the creation of various city books, there was a growing need to safely store the originals of important documents. These were collected in the so-called Threse, which soon formed a separate section of the emerging municipal archive. Although the holdings in the Hamburg State Archives are largely complete (with the exception of some losses due to the Second World War, among other things), the indexing by Johann Martin Lappenberg, which took place after the fire in Hamburg City Hall in 1842, still forms the basis for working with the material today. A comprehensive scholarly reappraisal remained a desideratum for a long time.